Aleutian Cackling Goose Branta hutchinsii leucopareia use of pastures in relation to livestock management - Spragens, Kyle M.; Black, Jeffrey M.; Johnson, Matthew D. (Wildfowl, 2015)
The recovered Aleutian Cackling Goose Branta hutchinsii leucopareia population nowadays relies during spring on livestock-grazed pastures along the coast of Humboldt and Del Norte Counties, northern California, USA. Selection of these foraging sites has however put geese in direct competition with livestock, which in turn has led to increased actions to reduce economic impacts to local farmers. We assessed forage characteristics between the two primary livestock grazing regimes that shape this landscape of beef cattle ranches and dairy cow farms. Peak counts and densities of Aleutian Cackling Geese were associated with the chronology of highest crude protein concentrations and low forage heights, but the timing did not coincide with greatest spatial distribution of use across this staging area. Grass crude protein concentrations peaked in February and were generally higher in dairy pastures than in beef pastures. However, use of dairy pastures was not observed until a month after staging commenced in this region. We encourage wildlife land managers to provide a successional range of short sward high protein pasture, by improving areas subject to invasion by salt tolerant plants, low in digestibility, in the coastal region and by irrigation in the uplands. These two mechanisms are likely to deliver more grassland of better quality for Aleutian Geese, and to encompass temporal and spatial shifts that occur on this landscape throughout the spring staging period.